Diagrammatic representation and inference : 9th international conference, Diagrams 2016, Philadelphia, PA, USA, August 7-10, 2016 : proceedings /: 9th international conference, Diagrams 2016, Philadelphia, PA, USA, August 7-10, 2016 : proceedings. (2016) - Unknown
No abstract available